PENERAPAN METODE SNMP (SIMPLE NETWORK MANAGEMENT PROTOCOL) DALAM OPTIMALISASI KINERJA JARINGAN KOMPUTER STUDI KASUS PADA IDN BOARDING SCHOOL - Husein; Gunawan, Dedi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This study aims to analyze and optimize the performance of the IDN Boarding School computer network using the SNMP (Simple Network Management Protocol) method. Computer network infrastructure in schools is an essential aspect that plays a key role in supporting the learning and management process. With rapid growth in usage and increasing network complexity, network performance often becomes a challenge. This research involved collecting data using SNMP to monitor and analyze network performance at IDN Boarding School, including measuring bandwidth usage, latency, and data transfer rates. The collected data is then analyzed in depth to identify weaknesses in the network that could potentially lead to unsatisfactory performance. Once the problem is identified, this study will recommend repair and optimization solutions including selecting appropriate hardware, optimal configuration, and implementing effective network management measures. SNMP methods will be used to track the implementation of innovative solutions and measure their impact on network performance. We hope that the results of this study will provide valuable information to IDN Boarding Schools on strategies to improve and optimize their networks. By implementing SNMP, schools can increase network resource efficiency, reduce network interference, and increase user satisfaction by up to 35%.